2017
DOI: 10.12968/jowc.2017.26.sup10.s4
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing outcomes in a diabetic foot ulcer outpatient clinic at an acute care hospital: a retrospective study

Abstract: Our findings are the first to demonstrate the benefits of chiropodists leading an acute care outpatient clinic in the management of DFUs in Canada and delivers wound healing outcomes equivalent to or exceeding those previously published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Finally, 18 articles with 5819 random individuals in total included in this study met the inclusion criteria and were enrolled to this meta-analysis. 10,11,[13][14][15][20][21][22][29][30][31][32][33][34][35][36][37][38] The literature review and selection process were minutely demonstrated in a flow diagram (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Finally, 18 articles with 5819 random individuals in total included in this study met the inclusion criteria and were enrolled to this meta-analysis. 10,11,[13][14][15][20][21][22][29][30][31][32][33][34][35][36][37][38] The literature review and selection process were minutely demonstrated in a flow diagram (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…However, only few studies have evaluated the role of such an interdisciplinary team approach in the management of DFUs. In Canada, only four recent studies [25][26][27][28] evaluated that approach, and all of them found positive outcomes in terms of wound healing and reduction of complications.…”
Section: Introductionmentioning
confidence: 99%
“…But this treatment is expensive and requires frequent hospitalizations. 21 Recently, topical drugs have been considered because of their low costs and patient compliance. One mechanism of topical drugs is their enzymatic debridement property.…”
Section: Discussionmentioning
confidence: 99%